Nutrientes que necesita nuestro cuerpo para mantenernos saludables - Corrales Portal, María Julia (2019)
This sufficiency work has been prepared for children of the first grade of primary education of the Educational Institution No. 800014 “Juan Pablo II.” Of the city of Trujillo in 2019, with the theme entitled: Nutrients that our body needs to keep us healthy In which the Indaga competition develops through scientific methods to build their knowledge. The purpose of this competence is to achieve a scientific literacy that makes them able to transfer or apply the knowledge acquired to new situations and real learning contexts._x000D_ In this sense, it is important that our students have basic knowledge based on the following great ideas of science. In the elaboration of the session we have worked with the didactic processes of the area of science and technology._x000D_ The strategies will allow students to strengthen their ability to assume a critical and reflective position so that they become increasingly involved in decision making and scientific skills.